Transformational Leadership, Employee Engagement and Commitment to Change: A Comparison Between Family and Non-family Corporations - Balgos, Marcial Orlando A, Jr (Archīum Ateneo, 2011)
This study examined the differences in transformational leadership, employee engagement and commitment to change between family and non-family firms that had undergone transformation in the past five years. Employee engagement was also tested for mediation in the relationship between transformational leadership and commitment to change. 1,091 employees from 21 Filipino corporations, one third of which are family firms, answered a 42-item survey questionnaire. As hypothesized, there were significant differences in transformational leadership and employee engagement between family and non-family corporations. In contrast to previous studies, non-family corporations scored higher on both variables than family corporations. No significant difference was noted in commitment to change between the two types of organizations. In addition, the study found that employee engagement partially mediates the relationship of transformational leadership and employee commitment. The results of this study add value to our understanding of how transformational leadership can influence employee engagement and commitment to change. On the practical side, leaders in the different types of organizations can find ways to strengthen their transformational leadership behaviors that increase employee engagement and in turn, lead to commitment to change.